Purification and partial characterization of the principal deoxyribonucleic acid polymerase from Mycoplasmatales. - Mills, L B (1977)
In this report we present the first description of the isolation and partial characterization of the deoxyribonucleic acid (DNA) polymerase activity from two species of Mycoplasmatales, Mycoplasma orale type 1 and M. hyorhinis. We have identified only a single DNA polymerase species in the mycoplasma crude extracts, and the enzymes from the two organisms are very similar in their structural and enzymatic properties. The purified polymerase from each source has a specific activity of greater than 50,000 U/mg of protein, a sedimentation coefficient of 5.6s, and an estimated molecular weight by gel filtration of 130,000. On sodium dodecyl sulfate-polyacrylamide gel electrophoresis, the most highly purified M. orale fraction contains a single major protein band of 130,000 daltons, which we believe may represent the polymerase protein. The enzymes are most reactive with gapped (activated) DNA and show a marked preference for this primer template over oligodeoxyribonucleotide-initiated homoribo- or homodeoxyribo-polymers. The most purified preparations are devoid of contaminating endonuclease activity and also appear to lack associated 5' leads to 3'- or 3' leads to 5'-exonuclease activities, as determined by highly sensitive assays. The absence of the 3' leads to 5'-exonuclease is particularly remarkable in that this activity is essentially ubiquitous among the DNA polymerases that have thus far been characterized from procaryotes.